Dynamics of Idxenergy Stock Returns: A Comprehensive Analysis of GDP, Exchange Rates, DJIA Index and Oil Prices - Rachmawati; Fadila, Ardhiani (Formosa Journal of Sustainable Research, 2024)
The movement of stock returns is a complex phenomenon that can be influenced by a number of factors, both macroeconomic and global factors. This study aims to explore the relationship and understand the extent to which these factors affect stock return movements, especially in the context of macroeconomic and global dynamics. The population of this study consists of companies listed in the IDXENERGY sector. Purposive sampling is used as a sample selection technique and 30 companies that meet the criteria are obtained. Panel data regression analysis with a significance level of 5% was conducted using Eviews 13. The research findings show that GDP has a negative impact on stock returns, while exchange rates, DJIA Index, and world oil prices have a positive impact on stock returns